2016
DOI: 10.1117/1.jbo.21.12.121510
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative effects of wavefront shaping and optical clearing agent in optical coherence tomography

Abstract: Abstract. We demonstrate that simultaneous application of optical clearing agents (OCAs) and complex wavefront shaping in optical coherence tomography (OCT) can provide significant enhancement of the penetration depth and imaging quality. OCA reduces optical inhomogeneity of a highly scattering sample, and the wavefront shaping of illumination light controls multiple scattering, resulting in an enhancement of the penetration depth and signal-to-noise ratio. A tissue phantom study shows that concurrent applicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In addition to immersion OC, more sophisticated methods based on controlling of the incident light wavefront can be used for the suppression of impact of strong light scattering on focused beam degradation and may improve significantly the image quality in tissue depth. [276][277][278][279][280][281][282][283] Most of these techniques use spatial light modulators to compensate the many spatial degrees of freedom of light at its transport in the scattering medium. 280,281 It was found that at wavefront control the multiply scattered light forms a focus with a brightness that is up to a factor of 1000 higher than the brightness provided at transport of the uncontrolled beam.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to immersion OC, more sophisticated methods based on controlling of the incident light wavefront can be used for the suppression of impact of strong light scattering on focused beam degradation and may improve significantly the image quality in tissue depth. [276][277][278][279][280][281][282][283] Most of these techniques use spatial light modulators to compensate the many spatial degrees of freedom of light at its transport in the scattering medium. 280,281 It was found that at wavefront control the multiply scattered light forms a focus with a brightness that is up to a factor of 1000 higher than the brightness provided at transport of the uncontrolled beam.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%
“…25). 283 It was also shown that computational or analytical OC can be applied as a noninvasive method to evaluate concentration of cutaneous chromophores at deep tissues. 284 The analytical OC uses the ability of diffuse reflection spectroscopy to reconstruct distribution of a particular chromophore of interest, which is normally hidden on the background of absorption of stronger tissue chromophores such as hemoglobin, melanin, and water and strong light scattering.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al 21 demonstrate the capability of a combination method of LSI and skin optical clearing to describe in detail the dynamic response of cutaneous vasculature to vasoactive noradrenaline injection. Yu et al 22 demonstrated that simultaneous application of OCAs and wavefront shaping techniques in optical coherence tomography (OCT) can provide signi¯cant enhancement of penetration depth and imaging quality. Guo et al 23 used a mixture of fructose with PEG-400 and thiazone (FPT) as an optical clearing agent in mouse dorsal skin and the observation showed that the mixture OCA leads to an improved imaging performance in OCT angiography for the deeper tissues.…”
Section: Introductionmentioning
confidence: 99%
“…TOC in combination with other methods of optical image improvement such as wavefront shaping OCT and labeling by luminescent upconversion NPs also may help significantly for in situ imaging of lymph nodes. TOC technology is demonstrated as an effective tool for theranostics, that is, not only for deep tissue imaging but also for tissue ablation .…”
Section: Introductionmentioning
confidence: 99%